2017
DOI: 10.3390/rs9080823
|View full text |Cite
|
Sign up to set email alerts
|

Low-Altitude Aerial Methane Concentration Mapping

Abstract: Detection of leaks of fugitive greenhouse gases (GHGs) from landfills and natural gas infrastructure is critical for not only their safe operation but also for protecting the environment. Current inspection practices involve moving a methane detector within the target area by a person or vehicle. This procedure is dangerous, time consuming, labor intensive and above all unavailable when access to the desired area is limited. Remote sensing by an unmanned aerial vehicle (UAV) equipped with a methane detector is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
31
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(40 citation statements)
references
References 23 publications
(20 reference statements)
0
31
0
Order By: Relevance
“…One of the primary advantages of UAVs is that they are uniquely suited to characterizing methane plumes in three dimensions while flying in close proximity to the source, improving confidence in attribution. To date, various attempts have been made to measure methane from a UAV (Khan et al 2012, Brownlow et al 2016, Barchyn et al 2017, Cossel et al 2017, Emran et al 2017, Smith et al 2017. The first comprehensive study investigating UAV methanesensing potential focused on a single compressor station, which was monitored over a one-week period by a fixed-wing UAV (Nathan et al 2015).…”
Section: Unmanned Aerial Vehiclesmentioning
confidence: 99%
“…One of the primary advantages of UAVs is that they are uniquely suited to characterizing methane plumes in three dimensions while flying in close proximity to the source, improving confidence in attribution. To date, various attempts have been made to measure methane from a UAV (Khan et al 2012, Brownlow et al 2016, Barchyn et al 2017, Cossel et al 2017, Emran et al 2017, Smith et al 2017. The first comprehensive study investigating UAV methanesensing potential focused on a single compressor station, which was monitored over a one-week period by a fixed-wing UAV (Nathan et al 2015).…”
Section: Unmanned Aerial Vehiclesmentioning
confidence: 99%
“…Further marked improvement in the precision, price, and availability of UAV-mounted sensors should be expected in the near future. Small drone-carried sensors have much promise for safe close-up mapping of air with high methane mole fractions around major leaks, for example, in mapping the 3-D distribution of a plume from a leaking gas installation, and hence quantifying the flux (Emran et al, 2017).…”
Section: Location By Drone (Uav) Surveysmentioning
confidence: 99%
“…However, even an affordable metal oxide gas sensor showed some response when a hexacopter was made to fly at a relatively low altitude over a gas source [10]. A hexacopter equipped with a laser-based remote methane detector [11] was able to detect methane emission from the ground even from 25 m above a landfill site [12]. A gas distribution map can be obtained by scanning the area of interest with a multicopter equipped with such a gas detection device [10,12,13].…”
Section: Introductionmentioning
confidence: 99%
“…A hexacopter equipped with a laser-based remote methane detector [11] was able to detect methane emission from the ground even from 25 m above a landfill site [12]. A gas distribution map can be obtained by scanning the area of interest with a multicopter equipped with such a gas detection device [10,12,13]. Neumann et al reported results of gas source localization experiments using a quadcopter equipped with several different types of gas sensors (metal oxide, electrochemical, catalytic, and infrared sensors) [14].…”
Section: Introductionmentioning
confidence: 99%